A Fe 8 O 8 (OH) 8 Cl 1.35 Catalyst and its preparation method and use
The preparation process of Fe8O8(OH)8Cl1.35 catalyst is simplified by a one-step solid phase sintering method, solving the problems of synthesis difficulty and industrial application in traditional methods, and achieving efficient and stable catalyst production.
Patent Information
- Application Number
- CN202411529969.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-10-30
AI Technical Summary
In the prior art, it is difficult to achieve the stable synthesis of Fe8O8(OH)8Cl1.35 catalyst. Traditional hydrothermal method requires the addition of organic additives and pH control. The process is complex and the product purity is low, making it difficult to achieve industrial application.
By using a one-step solid phase sintering method, the raw material of ferric chloride hexahydrate is ground and heat-raising sintering is carried out in a container, and the temperature is controlled at 160-280°C, simplifying the process flow and avoiding multiple heat treatments and intermediate product separation steps.
The stable synthesis of Fe8O8(OH)8Cl1.35 catalyst is achieved, which reduces production costs, simplifies the process flow, improves yield and product light stability, and is suitable for large-scale industrial production.
Smart Images

Figure CN119038618B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to but is not limited to the technical field of photocatalytic materials, and particularly relates to a Fe8O8(OH)8Cl 1.35 Catalyst, preparation method and use thereof. Background Art
[0002] Photocatalytic technology uses sunlight to drive chemical reactions, splitting water to produce clean hydrogen, reducing carbon dioxide to high-efficiency chemical fuels, or degrading pollutants in industrial and domestic wastewater, thereby helping to address energy crises and alleviate environmental degradation. The core of semiconductor photocatalytic technology lies in the targeted development of semiconductor materials, or photocatalysts. Most traditional oxide semiconductor photocatalytic materials suffer from limited light absorption ranges, high electron-hole recombination rates, poor photostability, limited selectivity, and low carrier mobility. These shortcomings have prompted researchers to continuously explore and develop new semiconductor photocatalyst materials. Among various new photocatalysts, research on iron-based semiconductor photocatalysts is relatively limited. This is due to the relatively late start of research on the application of iron-based semiconductor materials in photocatalysis and the challenges of their photocatalytic performance, such as stability and visible light absorption capacity. While some literature has reported progress on various composite semiconductor photocatalysts based on titanium, zinc, and tungsten ferrites, as well as iron-based metal-organic frameworks, research specifically on iron-based semiconductor photocatalysts is relatively rare. This suggests that the research and application of iron-based semiconductor photocatalysts in photocatalysis requires further development and exploration. With the increasing demand for new photocatalysts, iron-based semiconductor photocatalysts will become an important research direction in the future. 1.35 Nanomaterials are a good semiconductor photocatalyst material, but the research on this material is extremely rare, and the synthesis method is only the traditional hydrothermal method, and most of them are prepared with organic active agents. This method is difficult to achieve industrial application due to its high equipment requirements, long reaction time, low product purity, generation of organic by-products, and difficulty in large-scale production. Therefore, there is a need for a Fe8O8(OH)8Cl 1.35 A method for preparing a catalyst. Summary of the Invention
[0003] In view of the problems existing in the prior art, the present invention provides a Fe8O8(OH)8Cl 1.35 Catalyst, preparation method and use thereof.
[0004] The present invention is achieved by: a Fe8O8(OH)8Cl 1.35 The catalyst is prepared by a simple one-step solid-phase sintering method, comprising the following steps:
[0005] (1) Grind the ferric chloride hexahydrate raw material.
[0006] (2) The ground ferric chloride hexahydrate powder with uniform particles is placed in a container, and then the ferric chloride hexahydrate powder is placed in a heating device, and a temperature rising program is set to sinter.
[0007] (3) The temperature is lowered to room temperature, the sludge product obtained by sintering is cleaned, and the cleaned product is dried to obtain Fe8O8(OH)8Cl 1.35 catalyst.
[0008] Furthermore, in step (1), the ferric chloride hexahydrate raw material needs to be ground in a dry environment to prevent hydrolysis of the raw material.
[0009] Furthermore, in step (2), the amount of raw materials loaded into the container should be no less than half of its capacity, otherwise other by-products are likely to be generated. For example, it can be 2 / 3 of the container volume.
[0010] Furthermore, in step (2), the container should be covered with a lid after loading the raw materials to prevent the product from volatilizing.
[0011] Furthermore, in step (2), the programmed heating rate is 10°C / min, and the calcination temperature is maintained at 160-280°C, for example, 200°C.
[0012] According to the present invention, in step (4), the muddy product is brown and contains a variety of soluble impurities, and needs to be washed with water. As an illustrative example, it is ultrasonically cleaned with deionized water three times, centrifuged and then dried and collected.
[0013] Furthermore, the sample loading volume should be greater than half of the container volume.
[0014] Furthermore, in step (2), the sintering working atmosphere is air.
[0015] Furthermore, in step (3), the calcination temperature is 160-280°C.
[0016] Another object of the present invention is to provide a Fe8O8(OH)8Cl 1.35 Fe8O8(OH)8Cl prepared by the preparation method of the catalyst 1.35 The catalyst has a microstructure of a rod-shaped cluster structure composed of nanoparticles, and the average particle size of a single nanorod is about 5-300nm.
[0017] Preferably, the average particle size is 50-100 nm, and more preferably, the average particle size is 100 nm.
[0018] During the preparation process, it is prepared by a simple one-step calcination method and is carried out at low temperature without applying high temperature.
[0019] Another object of the present invention is to provide a Fe8O8(OH)8Cl 1.35 Catalyst used for photocatalytic hydrogen production. Fe8O8(OH)8Cl 1.35 The photocatalytic performance of hydrogen production from water splitting can reach 2.05 μmol g -1 h -1 .
[0020] In combination with the above technical solutions and the technical problems solved, the advantages and positive effects of the technical solutions to be protected by the present invention are as follows:
[0021] First, due to Fe8O8(OH)8Cl 1.35 The material is not easy to synthesize stably and occasionally appears as an intermediate product in chemical synthesis. Related research is relatively rare, and the hydrothermal synthesis method used in the rare literature requires the addition of organic additives and the control of pH to promote the stable synthesis of the material. The present invention provides a new preparation method of Fe8O8(OH)8Cl 1.35 The material method, that is, the one-step calcination method, is to directly place the raw materials in a muffle furnace and calcine them to prepare stable Fe8O8(OH)8Cl 1.35 The preparation method has low-cost raw materials, simple and safe operation, high yield, and is easy to synthesize stably and mass-produce. The technical method provided by the present invention solves the problem of the difficulty in synthesizing the material stably. Compared with the traditional synthesis route, it does not require the use of organic additives and pH control, and the preparation process generates less harmful waste liquid, which is more friendly to the ecological environment.
[0022] Fe8O8(OH)8Cl of the present invention 1.35 Nanomaterials can be used as photocatalyst materials and have good photostability.
[0023] Second, the Fe8O8(OH)8Cl 1.35 The material can use solar energy to decompose water to produce hydrogen, and can also degrade organic pollutants, which is of great significance to environmental protection; Fe8O8(OH)8Cl 1.35 The material exhibits good activity in the photocatalytic process and is expected to improve the conversion efficiency of solar energy to chemical energy, which has potential value for the development of sustainable energy technology; cost-effectiveness, the catalyst raw materials involved in the present invention are easy to obtain, low-cost, can be mass-produced and maintain their photocatalytic performance, it is more cost-effective than some existing photocatalysts, thereby lowering the economic threshold for clean energy and sewage treatment; nanomaterials usually have unique physical and chemical properties, Fe8O8(OH)8Cl 1.35 The research and application of nanocatalysts will promote technological progress in related fields, create new scientific research results and patents, and increase their commercial value.1.35 The expected benefits and commercial value of the material as a photocatalyst lie in its potential applications in environmental protection, energy conversion, cost-effectiveness, and technological innovation. Of course, the specific economic benefits also need to consider actual production costs, market acceptance, and the feasibility of large-scale application.
[0024] The technical solution of the present invention fills the technical gap in the industry at home and abroad: At present, about Fe8O8(OH)8Cl 1.35 The research on the material is still relatively rare, and its synthesis method, structural characteristics, potential applications, etc. need to be studied and developed urgently. The technical solution provided by the present invention adopts a simple one-step solid-phase calcination method, directly calcining the raw materials at an appropriate temperature, and completing the preparation of Fe8O8(OH)8Cl in one step without acid or alkali regulation and template additive conditions. 1.35 Catalyst. This technology fills Fe8O8(OH)8Cl 1.35 There are gaps in areas related to material synthesis methods and solar energy conversion applications.
[0025] The technical solution of the present invention solves the technical problems that people have been eager to solve but have never been able to achieve success: the one-step calcination method avoids the multiple heat treatments and intermediate product separation steps in the traditional synthesis method, shortens the entire production cycle, and due to the omission of complex post-processing steps, the conversion rate of raw materials to target products is higher, which helps to improve the overall yield; simplifying the process can reduce energy consumption, which is particularly important for large-scale industrial production. The simplicity and ease of operation of the one-step calcination method makes it easier to scale up the process to industrial production scale, which is conducive to reducing the manufacturing cost of unit products; by precisely controlling the calcination temperature and time, the microstructure and physical and chemical properties of the final product can be better regulated to ensure the consistency of product quality. The technical solution of the present invention can simplify the production process, improve yield, save energy and reduce consumption, scale production, and improve quality controllability.
[0026] Third, the technical solution of the present invention solves many problems in the prior art in industrial applications and brings about significant technological progress, as shown in the following:
[0027] 1. The complexity of the preparation process.
[0028] Existing technical issues: Traditional processes for preparing similar catalysts are often complex, often requiring multiple chemical reactions or high-temperature treatments, and involving tedious solvent preparation and handling, which increases time costs and process complexity. Furthermore, these methods have significant environmental impacts and high waste disposal costs.
[0029] Technological Advancement: This invention utilizes a one-step solid-phase sintering method, avoiding cumbersome liquid-phase reactions or multi-step chemical treatments. Through simple grinding, sintering, and cleaning steps, a highly efficient catalyst can be quickly obtained, significantly reducing process complexity and production costs. This process not only simplifies the process but is also more environmentally friendly, reducing solvent use and waste emissions, thereby enhancing process sustainability.
[0030] 2. The problem of unstable or uneven catalyst performance.
[0031] Existing technical problems: Many traditional catalysts are prone to problems such as unstable performance and uneven activity during the preparation process, which affects their application effect in actual industrial reactions. Especially in multiphase reactions, the activity of the catalyst will be affected by the surface morphology and structural heterogeneity.
[0032] Technological progress: This invention ensures the Fe8O8(OH)8Cl 1.35 The structural uniformity and stability of the catalyst. The grinding process increases the specific surface area of the material. The oxide and chloride structures formed during sintering are tightly bonded, creating more stable catalytic active sites and ensuring the stability and uniformity of the catalyst under different reaction conditions. This technological improvement significantly improves the performance consistency of the catalyst and enhances its reliability in industrial applications.
[0033] 3. The problem of high production costs.
[0034] Existing technical problems: Traditional catalyst preparation processes usually involve high-temperature multi-step treatments, high equipment requirements, harsh reaction conditions, and long production times, resulting in high production costs and making it difficult to meet the needs of large-scale industrial applications.
[0035] Technological Advances: The solid-phase sintering method of this invention eliminates the need for complex equipment and high-cost raw materials. Instead, it efficiently produces catalysts through a simple high-temperature sintering process. This method reduces raw material and energy consumption, requires relatively simple process equipment, and facilitates scalable catalyst production, reducing production costs for large-scale applications. This cost-effective process is suitable for industrialization, particularly for large-scale production of catalysts.
[0036] 4. The problem of insufficient catalytic efficiency and environmental performance.
[0037] Problems with existing technologies: Traditional catalysts exhibit certain catalytic efficiency in heterogeneous reactions, but their activity tends to decay as the reaction time increases. Furthermore, harmful by-products are produced during the preparation of these catalysts, making them environmentally unfriendly.
[0038] Technological progress: Fe8O8(OH)8Cl prepared by the present invention 1.35The catalyst not only exhibits high catalytic activity in heterogeneous reactions but also possesses excellent structural stability and long-lasting catalytic capacity, maintaining high catalytic efficiency for an extended period. Furthermore, this method does not involve the use of hazardous chemicals, and byproducts are removed through water washing, making the entire process clean and environmentally friendly. This environmentally friendly production method further enhances the catalyst's application value and meets the current industry demand for green manufacturing.
[0039] This invention, through a simple, one-step solid-phase sintering method, addresses existing issues such as complex processes, unstable catalyst performance, high production costs, and insufficient environmental performance. Its significant technological advancements are reflected in simplified processes, improved catalyst performance, reduced production costs, and environmental friendliness. It has broad industrial application prospects and is particularly suitable for large-scale production and application in the catalysis field.
[0040] Fourth, the parameter setting and process optimization of the present invention solves multiple problems in the prior art in industrial applications and achieves significant technological progress, which is specifically reflected in the following aspects:
[0041] 1. Technical problems solved.
[0042] (1) Low catalyst purity leads to unstable performance.
[0043] In existing technologies, the difficulty in effectively removing impurities during the preparation process leads to unstable catalyst purity and performance, which directly affects the effectiveness of the catalyst. In particular, the accumulation of impurities during multiple catalytic reactions can accelerate catalyst deactivation.
[0044] (2) The sintering process is not precisely controlled and the crystal phase stability is poor.
[0045] In traditional catalyst preparation processes, the sintering temperature and heating rate are difficult to accurately control, resulting in unstable crystal structure, which in turn affects the catalytic activity and durability of the catalyst.
[0046] (3) Raw material hydrolysis problem.
[0047] Raw materials like ferric chloride hexahydrate are susceptible to hydrolysis in humid environments, causing structural changes that can affect the composition and performance of the catalyst. Existing technologies lack environmental control for grinding and raw material handling, and this hydrolysis problem negatively impacts the process.
[0048] 2. Significant technological progress.
[0049] (1) High-precision measurement and control improve catalyst purity and stability.
[0050] The present invention effectively solves the problem of low catalyst purity by optimizing the catalyst preparation process, especially the precise setting of the cleaning and drying steps. Specifically, in step (3), impurities are completely removed by ultrasonic cleaning with deionized water and repeated centrifugation operations, so that the final Fe8O8(OH)8Cl 1.35 The catalyst has higher purity and more stable catalytic performance.
[0051] (2) Precise heating rate and sintering temperature control ensures crystal phase stability.
[0052] The present invention significantly improves the stability of the crystal phase by precisely controlling the heating rate (10°C / min) and calcination temperature (160-280°C) during the sintering process. This precise temperature control design avoids over-sintering or under-sintering, ensuring the stability of Fe8O8(OH)8Cl 1.35 The structural integrity of the catalyst is enhanced, thereby significantly improving its catalytic activity and service life.
[0053] (3) Hydrolysis control solves the problem of raw material stability.
[0054] In order to solve the problem of hydrolysis of raw materials during the preparation process, the present invention introduces a process of grinding ferric chloride hexahydrate in a dry environment in step (1), thereby avoiding the hydrolysis of the raw materials in a humid environment. Through this control, the chemical properties of the raw materials are fully protected, ensuring that Fe8O8(OH)8Cl 1.35 The stability of the catalyst components, thereby improving its final performance.
[0055] 3. Impact of industrial applications.
[0056] The present invention significantly improves the Fe8O8(OH)8Cl 1.35 The catalyst's purity, crystal phase stability, and catalytic performance make it highly competitive for use in industrial catalytic reactions. Its precise temperature control and material handling processes not only improve product quality but also reduce production costs, enhancing its market competitiveness. In particular, in fields such as environmental catalysis, waste gas treatment, and chemical catalysis, this invention can significantly improve reaction efficiency and reduce catalyst deactivation, providing a highly efficient and reliable technical solution for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 It is Fe8O8(OH)8Cl provided in Examples 1-4 of the present invention 1.35 Flow chart of the catalyst preparation method.
[0058] Figure 2 It is Fe8O8(OH)8Cl provided in Example 3 of the present invention 1.35Schematic diagram of the catalyst structure.
[0059] Figure 3 It is Fe8O8(OH)8Cl provided in Example 3 of the present invention 1.35 X-ray diffraction pattern of the catalyst.
[0060] Figure 4 It is Fe8O8(OH)8Cl provided in Example 3 of the present invention 1.35 UV-visible absorption spectrum of the catalyst.
[0061] Figure 5 It is Fe8O8(OH)8Cl provided in Examples 1-4 of the present invention 1.35 Photocatalytic hydrogen production performance diagram of the catalyst. DETAILED DESCRIPTION
[0062] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0063] like Figure 1 As shown, the embodiment of the present invention provides a Fe8O8(OH)8Cl 1.35 The catalyst is prepared by a simple one-step solid-phase sintering method, comprising the following steps:
[0064] (1) Grind the ferric chloride hexahydrate raw material.
[0065] (2) The ground ferric chloride hexahydrate powder with uniform particles is placed in a container, and then the ferric chloride hexahydrate powder is placed in a heating device, and a temperature rising program is set to sinter.
[0066] (3) The temperature is lowered to room temperature, the sludge product obtained by sintering is cleaned, and the cleaned product is dried to obtain Fe8O8(OH)8Cl 1.35 catalyst.
[0067] Fe8O8(OH)8Cl of the present invention 1.35 The catalyst is prepared using a one-step solid-phase sintering method, which is simple and efficient. The specific working principle is as follows:
[0068] The first step in the preparation process is to prepare a container for sintering. The container needs to be cleaned and dried to ensure a clean, impurity-free environment. Next, ferric chloride hexahydrate is prepared as the catalyst raw material. Grinding reduces the size of the ferric chloride hexahydrate particles, increasing their surface area. This provides an ideal physical foundation for the subsequent uniform heating and sintering reactions.
[0069] The second step is to evenly disperse the ground ferric chloride hexahydrate powder in a container and cover it with a lid to maintain the airtightness of the reaction environment. The container is placed in a heating device for precise temperature increase. During the sintering reaction, ferric chloride hexahydrate decomposes and oxidizes at high temperatures to produce Fe8O8(OH)8Cl 1.35 The heating process is strictly controlled to ensure that the reaction is complete and no impurities are introduced, and the formed chloride and oxide can be fully combined.
[0070] The third step, after sintering, is to cool the product to room temperature. This step is crucial: rapid cooling can cause structural changes or cracks in the product, while slow cooling ensures structural stability. The resulting product is a sludge-like substance containing incompletely reacted byproducts and residual reactants.
[0071] The fourth step is to repeatedly wash the cooled muddy product with appropriate deionized water to remove residual chloride and other impurities. The washed product needs to be dried to remove moisture and ensure the purity and structural integrity of the catalyst. The final Fe8O8(OH)8Cl 1.35 The catalyst has excellent physical and chemical properties and is suitable for a variety of catalytic reactions. This preparation method is simple and controllable, and can obtain Fe8O8(OH)8Cl with high catalytic performance in a relatively short time. 1.35 catalyst.
[0072] Example 1.
[0073] Weigh 3.0g ferric chloride hexahydrate medicine and be placed in mortar and grind. The powder after grinding is added to corundum crucible, covered with crucible lid, then placed in small muffle furnace, 10 DEG C / min is warming up to 180 DEG C, constant temperature calcination 2 hours, then naturally cool down. After room temperature, take out crucible, collect the brown mud at crucible bottom, add water to wash, remove impurity, then centrifugal enrichment, so repeatedly wash 3 times after, the khaki precipitate of enrichment is placed in 60 DEG C of forced air drying oven and is dried 12 hours.
[0074] Example 2.
[0075] 3.0g of ferric chloride hexahydrate medicine is weighed and placed in a mortar and ground. The ground powder is added to a corundum crucible, the crucible lid is covered, and then placed in a small muffle furnace. 10 ° C / min is warming up to 200 ° C, constant temperature calcined for 2 hours, and then naturally cooled. After room temperature, the crucible is taken out, the brown mud at the bottom of the crucible is collected, water is added to clean, impurities are removed, and then centrifugal enrichment is performed. After repeated cleaning 3 times, the khaki precipitate of enrichment is placed in a forced air drying oven at 60 ° C and dried for 12 hours.
[0076] Example 3.
[0077] Weigh 3.0g ferric chloride hexahydrate medicine and be placed in mortar and grind. The powder after grinding is added to corundum crucible, covered with crucible lid, then placed in small muffle furnace, 10 DEG C / min is warming up to 220 DEG C, constant temperature calcination 2 hours, then naturally cools down. After room temperature, take out crucible, collect the brown mud at crucible bottom, add water to wash, remove impurity, then centrifugal enrichment, after so repeatedly washing 3 times, the khaki precipitate of enrichment is placed in 60 DEG C of forced air drying ovens and is dried 12 hours.
[0078] Example 4.
[0079] Weigh 3.0g ferric chloride hexahydrate medicine and be placed in mortar and grind. The powder after grinding is added to corundum crucible, covered with crucible lid, then placed in small muffle furnace, 10 DEG C / min is warming up to 240 DEG C, constant temperature calcination 2 hours, then naturally cool down. After room temperature, take out crucible, collect the brown mud at crucible bottom, add water to wash, remove impurity, then centrifugal enrichment, so repeatedly wash 3 times after, the khaki precipitate of enrichment is placed in 60 DEG C of forced air drying oven and is dried 12 hours.
[0080] Fe8O8(OH)8Cl prepared in Example 1-4 1.35 Photocatalysts were used to test the performance of photocatalytic water splitting.
[0081] 20 mg of catalyst powder was added to a photocatalytic reactor, followed by 20 mL of an appropriate deionized water solution containing 10% methanol. Stirring was continued, and nitrogen was bubbled through the system for 60 minutes to remove oxygen. The nitrogen flow was then stopped and the reactor sealed. A xenon lamp simulating natural light was placed above the reactor and turned on to initiate the photocatalytic reaction. The gas produced by water decomposition within the system was sampled and analyzed periodically using the photocatalytic system's built-in gas chromatography system, with samples taken every 0.5 hours. Each sample was analyzed five times to determine the types and contents of the gaseous products produced by the photocatalytic water decomposition reaction.
[0082] Figure 5 It is Fe8O8(OH)8Cl provided in Examples 1-4 of the present invention 1.35 The photocatalytic hydrogen production performance diagram of the catalyst shows that Examples 1-4 all have relatively stable photocatalytic hydrogen production performance, among which Fe8O8(OH)8Cl prepared in Example 3 1.35 The photocatalyst can produce hydrogen by photolysis of water up to 2.05 μmol g -1 h -1 .
[0083] The above description is only a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any modifications, equivalent substitutions and improvements made by any technician familiar with this technical field within the technical scope disclosed by the present invention and within the spirit and principles of the present invention should be covered by the scope of protection of the present invention.
Claims
1. Fe8O8(OH)8Cl 1.35 The method for preparing a catalyst is characterized in that: The following steps are involved: (1) Grinding ferric chloride hexahydrate raw material; (2) placing the ground ferric chloride hexahydrate powder with uniform particles in a container and covering it with a lid to maintain the airtightness of the reaction environment, then placing the ferric chloride hexahydrate powder in a heating device, setting a temperature rising program, and sintering; (3) The temperature is lowered to room temperature, the sludge product obtained by sintering is cleaned, and the cleaned product is dried to obtain Fe8O8(OH)8Cl 1.35 catalyst; In step (2), the container is loaded with raw materials in an amount greater than half of the volume of the container; In step (2), the programmed heating rate is 10 °C / min, and the calcination temperature is maintained at 160-280 °C; In step (2), the sintering working atmosphere is air.
2. Fe8O8(OH)8Cl as claimed in claim 1 1.35 The method for preparing a catalyst is characterized in that: In step (1), the ferric chloride hexahydrate raw material is ground in a dry environment to prevent the raw material from hydrolysis.
3. Fe8O8(OH)8Cl as claimed in claim 1 1.35 The method for preparing a catalyst is characterized in that: In step (3), ultrasonic cleaning is performed with deionized water for 3 times, and the mixture is dried and collected after centrifugation.
Citation Information
Patent Citations
One-step synthesis of nanometer layered porous material of FeOCl and application thereof
CN106698525A
METHOD OF DISPOSAL OF SPENT ETCHING SOLUTIONS CONTAINING IRON (II) SULFATES AND CHLORIDES
RU2010101213A